A Comparison Study between Green Synthesis of Microwave Irradiation and Solvent Evaporation Methods in The Formation of p-Methoxycinnamic Acid-Succinic Acid Cocrystals - Sulistyowaty, Melanny Ika; Setyawan, Dwi; Prameswari, Putu Pradnya Mimba; Susilo, Raden Joko Kuncoroningrat; Amrillah, Tahta; Zaini, Erizal; Zidan, Sabry A. H. (Science and Technology Indonesia, 2024)
Cocrystal of p-Methoxycinnamate acid-succinic acid has been produced by microwave irradiation and solvent evaporation methods. Cocrystals are formed using succinic acid as the coformer at a molar ratio of 1:1. The formation of cocrystal can be done by solvent evaporation method and microwave radiation method. Physicochemical properties have been studied by FT-IR, DSC, PXRD, and SEM analysis. The solubility test was carried out with pH 6.8 phosphate buffer at a temperature of 25±0.5°C for 5 hours and the dissolution test was carried out with 900 mL pH 6.8 phosphate buffer at a temperature of 37±0.5°C with the speed of 75 rpm using a paddle-type dissolution test apparatus. The solubility of PMCA has increased its solubility in cocrystals by the solvent evaporation method by 1.19 times and by the microwave radiation method by 1.16 times compared to PMCA. The dissolution rate of the cocrystals of the solvent evaporation method increased by 3.50 times and the cocrystals of the microwave radiation method increased by 2.29 times compared to PMCA.